Letter (copy) : Food for Spain - Tewson, Vincent
030-0209-001 HVT/FC/219. Secretary's. 7th February, 1938. Mr. E. Winstanley, The Co-operative Wholesale Society Ltd., 1, Balloon Street, MANCHESTER. Dear Mr. Winstanley, FOOD FOR SPAIN. I thank you for your letters of the 4th and 5th instant enclosing Bill of Lading in respect of the goods sent per the s. s. "Plover'', together with invoices. I am enclosing herewith cheque value £2,580. 5s. to cover the cost of the goods, together with freight charges, etc., and I shall be glad to receive your receipt for this amount in due course. Yours sincerely, Assistant Secretary. Cheque. 292/946/30/209